2016
DOI: 10.15587/1729-4061.2016.80070
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining anisotropic hexaferrites for the base layers of microstrip shf devices by the radiation-thermal sintering

Abstract: Радіаційно-термічним спіканнням (РТС) отримані зразки анізотропних полікристалічних гексаферитів BaFe 12 O 19 , BaFe 12-х Al х O 19 (з добавками Ni, Ti, Mn), SrFe 12 O 19 і SrFe 12-х Al х O 19 (з добавками Ca, Si) для феритових розв'язуючих приладів. Суть технології РТС полягає в пресуванні в сильному магнітному полі сирих заготовок і їх подальшому спіканню в пучку швидких електронів Ключовi слова: гексагональний ферит, радiацiйно-термiчне спiканння, пресування, магнiтне поле, текстура Радиационно-термическим … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A synthesis method was previously developed to reduce the temperature and time of ferrite synthesis; it employs heating of the initial reagents by an electron beam with energies above 1 MeV [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. High electron energies provide the possibility of volumetric heating of the synthesized samples, and the electron penetration depth depends on the density of the samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A synthesis method was previously developed to reduce the temperature and time of ferrite synthesis; it employs heating of the initial reagents by an electron beam with energies above 1 MeV [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. High electron energies provide the possibility of volumetric heating of the synthesized samples, and the electron penetration depth depends on the density of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…The electron-beam heating method was used to synthesize ferrites of various compositions, including spinel lithium, lithium-zinc and manganese-zinc ferrites, and hexagonal ferrites [ 35 , 38 , 39 , 40 , 41 , 42 ]. In [ 43 , 44 , 45 ], it was shown that this heating method increases the rate of solid-phase interaction between the initial reagents, which significantly decreases the ferrite synthesis temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the impact of ionizing radiation fluxes has been developed in the production and modification of materials. In this case, the fundamental phenomenon of a multiple increase in the process of synthesis of multicomponent powder materials [5][6][7][8][9][10][11][12][13] and sintering [14][15][16][17][18][19][20][21][22][23][24] under radiation-thermal (RT) conditions was discovered. The processes of lithium-titanium ferrites sintering have been most fully studied under such specific conditions of the combined action of high temperatures and intense electron flows [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%